Vanek’s tumor: a rare differential diagnosis of colonic submucosal lesions - Berrospi-Castillo, Diego (2023)
Gastrointestinal submucosal lesions represent a diagnostic challenge, including benign or malignant lesions, so they are identified more accurately by histopathological study accompanied by immunohistochemistry. This is a case of a 21-year-old man with a bleeding submucosal lesion in the cecum. The patient underwent a right colectomy. Microscopic finding was compatible with Vanek's tumor.